The Influence of Total Quality Management on Organizational Performance on Bank Services - Dian Awalia Ramadhanty; Melya Utami Putri; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2023)
Total Quality Management or TQM is applied in every business sector, including finance. Currently, there are intense competition between banks, as well as changes in customer demands and expectations. Therefore, banks as service providers must maintain, increase satisfaction, and meet the needs of their customers by providing the best quality products and services. The best quality products and services will result in better organizational performance. The method used in this literature study is a descriptive method with a qualitative approach, to explore data and information related to the application of TQM in bank services to improve service quality and answer theoretical problems. This study aims to determine how the effect of the application of TQM on the quality of bank services and what factors affect bank customer satisfaction. The results of this study prove that TQM can be the key to bank managerial success to increase customer satisfaction. There is a direct relationship and interrelationship between TQM and organizational performance. Good organizational performance depends on an efficient system so that a holistic approach to quality management produces more optimal results